Preliminary development of enterprising Tongkat Ali herbal capsule authenticated to be original by Universiti Malaysia Pahang scientists - Vejayan, Jaya; Yusoff, M. M.; Mohamed, Aini Norhidayah (2018)
Eurycoma longifolia is widely known for its aphrodisiac properties. Due to this, abundant of the E. longifolia based products are sold in the market without any specific regulation. To control the quality and authentication of E. longifolia product, the common marker used to authenticate E. longifolia is eurycomanone. This project is to develop E. longifolia product according to Malaysian Standard as well as to obtain approval of MAL number from National Pharmaceutical Regulations Agency (NPRA). HPLC analysis has been used as quantitative and qualitative analysis to determine the presence and quantity of eurycomanone content in water extract of E. longifolia derived Tongkat Ali Capsules by Indigenous People (TAC-IP) and Tongkat Ali Capsule in House Formulation (TAC-IHF). TAC-IP is herbal capsules manufactured by the indigenous people of Kampung Bukit Cermin, Perak without NPRA approval and sold to customers for the past 15 years. While TAC-IHF is a prototype manufactured in this project specifically to be standardized and tested prior to NPRA registration fulfillments. The result indicated the quantity of eurycomanone in E. longifolia root water extract is 1.24 (w/w) %. The formulation of TAC-IHF has been done by standardizing the percentage of eurycomanone content into 0.80 w/w %. This percentage was chosen as it is in accordance to the Malaysian Standard which stated to be in the range of 0.8 - 1.5 w/w% of eurycomanone. The formulation of TAC-IHF was to adopt the method used by the Indigenous people i.e. by sieving the powdered root. Several requirements of NPRA was fulfilled which is heavy metal test, microbial load test, uniformity of weight test and labeling process. Besides that, the additional test was conducted which is uniformity of eurycomanone content in each capsule by HPLC. It was conducted to gauge the percentage of eurycomanone in each capsule to be similar. Lastly, a survey to investigate the acceptance and effectiveness of TAC-IP was carried out. The proposed method and analyzing showed TAC-IHF to be standardized and in accordance to the Malaysian standard and partially fulfilled requirements of NPRA. Next, the powdered material weighing 1.5kg was submitted to Dong Foong Manufacturing Sdn Bhd (hired contract manufacturer) for the MAL number approval. After a series of documentation, GMP capsulation, testing and many more procedures the manufactured capsules submitted to NPRA. Currently, the capsules obtained clearance at early phases and pending MAL number approval.